2012
DOI: 10.1530/erc-12-0092
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate and human ether-a′-go-go-related gene potassium channels modulate migration in human anaplastic thyroid cancer cells

Abstract: Anaplastic thyroid cancer (ATC) is the most aggressive form of human thyroid cancer, lacking any effective treatment. Sphingosine 1-phosphate (S1P) receptors and human ether-a 0 -go-go-related gene (HERG (KCNH2)) potassium channels are important modulators of cell migration. In this study, we have shown that the S1P 1-3 receptors are expressed in C643 and THJ-16T human ATC cell lines, both at mRNA and protein level. S1P inhibited migration of these cells and of follicular FTC-133 thyroid cancer cells. Using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 34 publications
4
20
1
Order By: Relevance
“…For example, S1P activates inwardly rectifying K + currents (I K.ACh ) in ventricular myocytes with the involvement of S1P 1 and S1P 3 (Landeen et al, 2008) and the SUR2/K ir 6.2 channel via S1P 3 in mouse ventricular fibroblasts (Benamer et al, 2009, 2011). Although a direct regulatory effect of S1P 3 on potassium channel activity is not supported by the present results, this leaves three alternative possibilities as explanations for the significantly reduced input resistance and firing frequency in S1P3/ mice: first, other members of the large potassium channel family may be targeted by S1P 3 receptor signaling similar to a study in human anaplastic thyroid cancer cells where S1P down-regulates Kv11.1 regulation via S1P 2 (Asghar et al, 2012). Second, protein expression may be deregulated by mechanisms independent of transcription e.g., by microRNAs as shown for BK potassium channels (Pietrzykowski et al, 2008) or third, posttranslational modifications of ion channels such as protein phosphorylation or trafficking may be affected by S1P 3 receptor depletion (Johnston et al, 2010).…”
Section: Discussioncontrasting
confidence: 57%
“…For example, S1P activates inwardly rectifying K + currents (I K.ACh ) in ventricular myocytes with the involvement of S1P 1 and S1P 3 (Landeen et al, 2008) and the SUR2/K ir 6.2 channel via S1P 3 in mouse ventricular fibroblasts (Benamer et al, 2009, 2011). Although a direct regulatory effect of S1P 3 on potassium channel activity is not supported by the present results, this leaves three alternative possibilities as explanations for the significantly reduced input resistance and firing frequency in S1P3/ mice: first, other members of the large potassium channel family may be targeted by S1P 3 receptor signaling similar to a study in human anaplastic thyroid cancer cells where S1P down-regulates Kv11.1 regulation via S1P 2 (Asghar et al, 2012). Second, protein expression may be deregulated by mechanisms independent of transcription e.g., by microRNAs as shown for BK potassium channels (Pietrzykowski et al, 2008) or third, posttranslational modifications of ion channels such as protein phosphorylation or trafficking may be affected by S1P 3 receptor depletion (Johnston et al, 2010).…”
Section: Discussioncontrasting
confidence: 57%
“…Migration and Invasion Assays-Migration and invasion assays were performed as described previously (18). In some experiments, the cells were preincubated with 10 M KN-93, 100 M W-13 hydrochloride, or 2 M GsMTx-4 for 1 h, respectively, at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we have shown that S1P (100 nM, 6 h) inhibits migration and invasion of human anaplastic thyroid cancer C643 and follicular thyroid cancer FTC-133 cells towards lipid-stripped serum. This attenuated migration is mediated by S1P 2 and the Rho-ROCK pathway [ 10 ]. Interestingly, S1P promotes migration and invasion in human follicular thyroid cancer ML-1 cells [ 6 8 , 21 ] and increases the secretion and activity of MMP2 and MMP9 through S1P 1,3 [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Invasion assays were performed as described elsewhere [ 10 ]. Cells were grown in 0.2% FAF-BSA-containing serum-free medium (SFM) overnight before the start of an experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation